Laman web butik Radzuan Radziwill / Juriah Jalalus Shuti - Jalalus Shuti, Juriah (2001)
The website for Radzuan Radziwill Boutique is developed to enlarge the business runs by this boutique through the Internet. The user can retrieve information about its owner and staffs, the collection, activities, news and also ask questions. The user can buy clothes, accessories and scarfs, online. The member of The Radzuan Radziwill Boutique is able to buy clothes according to her measurement and choose the color, type of fabric, and type of fashion suitable for her. For the Administrator, a system is built to make it easier for them to manage any transaction made by the customer. The customer's information that is his/her personal data and transaction data are kept in the databAse. The Administrator can add, edit and delete any related product, staffs information and also customer's information.